Mekanisme Penagihan Piutang Negara Menggunakan Crash Program pada KPKNL Pekanbaru - Sari, Putri Ramita; Endang Sri Wahyuni (Politeknik Negeri Bengkalis, 2023)
This study aims to determine the mechanism for collecting state receivables before and after the implementation of the crash program mechanism and to find out what are the obstacles in collecting state receivables at the Pekanbaru KPKNL. This research is descriptive qualitative. Data collection was carried out by inter-views and documentation. The results of this study are, based on the procedures carried out by the Pekanbaru KPKNL before the implementation of the crash pro-gram mechanism was appropriate based on PMK No.240/PMK.06/2016. Whereas after the implementation of the crash program mechanism was in accordance with PMK Number 11/PMK.06/2022 while obstacles in collecting state receivables at the Pekanbaru KPKNL were caused by incomplete data from the debt guarantor, the debt guarantor was unable to pay off the debt, the debt guarantor did not have collateral and the business of the debt guarantor is not going well.